Surgical abdominal emergencies in disadvantaged area: Epidemiologic and therapeutic aspects. - Paluku Katswere, Josaphat; Attolou, Setondji Gilles Roger; Natta N’tcha, Habib N’Domè; MUPEPE KUMBA, ALEXIS; Liady, Akintola Loukoumanou; Kambasu, Talimula D; Mehinto, Delphin Kuassi (My University, 2018)
Introduction: Surgical abdominal emergencies remain a common topic in surgery, especially in under-equipped environments. Aim: To study the epidemiological, diagnostic and therapeutic aspects of these emergencies at the Savalou-Bantè Zonal hospital in Benin. Patients and methods: This was a prospective study that involved all patients operated for a surgical abdominal emergency at the Savalou-Bantè area hospital from November 1st, 2016 to August 31, 2017. Data were analyzed with Epi Info software 3.5.4 version. Results: Patients operated for an abdominal emergency represented 31.52% of the admissions to the service of emergencies. The sex-ratio was of 1.72. The average consultation time was 5 ± 2.14 days with extremes of 03 hours and 7 days. The abdominal pain was the chief complain with 74.22% admissions. Non-traumatic surgical abdominal emergencies were the most common with 125 cases or 97.66%. Acute appendicitis (58 cases, 45.31%), Acute generalized peritonitis (24 cases, 18.75%) and strangulated hernia (23 cases, 17.97%) were the main etiologies of surgical abdominal emergencies. The diagnosis was clinical in the majority of cases. An imagery examination for diagnostic purposes has been achieved among 34 patients or 26, 56%. The average time for surgical management was 15 hours. The exclusive spinal anesthesia with 85 cases or 66.41% was the more practiced. The approach was laparotomy among all patients. The Antibiotic therapy was probabilistic and systematic. The morbidity was 17.97% (23 cases) dominated by parietal suppurations (15 cases / 23); and mortality of 2.34%. Conclusion: Surgical abdominal emergencies are frequent. Their diagnosis is still mainly clinical and their care is burdened with a non negligible morbidity. Improvement of the technical tray would help to reduce postoperative complications.
Keywords: Abdominal emergencies; Appendicitis; Morbidity; Parietal suppuration; Peritonitis.